Information Technology Utilization in Senior High School Learning in Gorontalo: A Systematic Literature Review - Abdul Gani Fadhlulrahman S. H. Lihawa; Fandli Supandi; Afifah Farhanah Akadji (Fakultas Teknik, Universitas Negeri Makassar, 2026)
Purpose – This study critically examines patterns, challenges, and research gaps pertaining to information technology (IT) utilization in learning among senior high school (SMA) students in Gorontalo, Eastern Indonesiaa region characterised by significant infrastructure constraintswith the aim of generating evidence-based recommendations for contextually appropriate technology integration in secondary and vocational educational settings. Methods – A Systematic Literature Review (SLR) was conducted following the PRISMA 2020 protocol. A structured Boolean search across four databasesGoogle Scholar, Semantic Scholar, Garuda, and DOAJyielded 287 initial results. After two-stage screening and quality appraisal using an adapted CASP checklist, five peer-reviewed articles (2019–2025) were selected for thematic comparative synthesis. Findings – Three dominant themes emerged: the conditional effectiveness of digital learning platforms under adequate infrastructure; the primacy of teacher digital literacy over infrastructure availability as a predictor of implementation success (path coefficient = 0.67 vs. 0.43); and the strategic value of offline-capable mobile learning (SUS = 78.6). Gorontalo-specific data show 62% of SMA students rely exclusively on smartphones, only 56.9% of sub-districts have 4G coverage, and a critically low proportion of teachers received ICT training in the preceding two years, according to available provincial data. Research implications – The corpus of five studies reflects a genuine literature gap. Caution is warranted in generalising findings. Interventions addressing only device access, without commensurate teacher capacity development or offline content design, will yield suboptimal outcomes across SMA and SMK contexts in under-resourced regions. Originality – This review provides the first systematic synthesis specifically examining IT utilisation in secondary education within Gorontalo's regional context, offering an evidence-based foundation for more equitable educational technology policy in Eastern Indonesia.